Preparation method and application of alumina-doped high-temperature radar wave-absorbing coating
By doping alumina in the high-temperature radar absorbing coating and adopting two-step heat treatment technology, the cracking problem caused by volume shrinkage in a traditional coating in a high-temperature environment is solved, and higher density and high temperature stability are achieved.
Patent Information
- Application Number
- CN202411945076.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-26
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The cracking problem caused by volume shrinkage in a traditional high-temperature radar absorbing coating in an environment of 700°C or above affects its high-temperature stability and density.
Alumina-doped CaO-B2O3-SiO2 (CBS) microcrystalline glass is used as the matrix material, and a two-step heat treatment technology is used to generate a glass liquid phase to enhance the density and stability of the coating.
It significantly improves the density and high temperature stability of the coating, avoids cracking problems caused by volume shrinkage, and meets the stable use needs in a 700℃ environment.
Smart Images

Figure CN119662056A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of absorbing materials, and specifically relates to a preparation method and application of an aluminum oxide-doped high-temperature radar absorbing coating. Background Art
[0002] With the rapid development of radar detection technology, combat equipment and personnel are facing severe challenges in their survival. Therefore, improving the radar absorbing performance of aircraft, especially the radar absorbing performance of high-temperature components at temperatures of 700°C and above, has become the key to addressing this problem. For aircraft components with specific external structures, the surface modification of the alloy substrate by cold / hot coating (spraying) technology can significantly improve its radar absorbing effect without affecting the aerodynamic performance. Traditional radar absorbing coatings use organic matter (such as resin, silicone, etc.) as coating matrix materials and magnetic alloys (Fe-based and other magnetic alloys) as filling materials. By adjusting the ratio of the two and the preparation process, a dense coating is formed at room temperature, showing excellent radar absorbing performance and can remain stable below 350°C. However, in a high temperature environment, organic matter will undergo carbonization and cracking. At the same time, due to the mismatch of the thermal expansion coefficient between the coating and the substrate, thermal stress accumulation leads to cracking and failure, which is difficult to meet the current use needs.
[0003] Using Al 2 O 3 、Al 2 O 3 -TiO 2 High-temperature ceramic materials such as YSZ are used as the matrix material of radar absorbing coatings, and high-temperature resistant Fe-based magnetic alloys are used as filling materials. Through the thermal spraying process, they are completely melted and metallurgically bonded with the alloy substrate, which can significantly improve the bonding strength of the coating. However, this type of high-temperature ceramic material usually has a large dielectric constant and a high density, which is not conducive to the lightweight and broadband design of the coating. In addition, the layered structure formed by thermal spraying has natural oxygen channels that allow oxygen to enter the coating. Fe-based magnetic alloys are extremely susceptible to oxidation corrosion in high-temperature environments, which reduces the high-temperature stability of the coating.
[0004] In contrast, CaO-B 2 O 3 -SiO 2 (CBS) glass-ceramics is considered an ideal high-temperature matrix material due to its low density, thermal conductivity and dielectric constant. However, due to the rapid cooling and heating effect during thermal spraying, the CBS phase in the coating is usually an amorphous phase and a porous structure. The coating can soften and fill the pores during heat treatment at 800℃ (and above) to densify the coating, but the high temperature allows the coating to reach the crystallization activation energy, thereby precipitating β-CaSiO 3During the crystallization process, the glass phase will shrink in volume, resulting in tensile stress between the coating and the alloy substrate, which will lead to cracking and failure of the coating. Therefore, it is urgent to develop a new method to overcome the cracking problem of CBS-based radar absorbing coatings during heat treatment and prepare high-density high-temperature radar absorbing coatings that can be stably used in a high-temperature environment of 700°C. Summary of the invention
[0005] In order to solve the above problems or shortcomings, the current CaO-B 2 O 3 -SiO 2 The cracking failure problem of (CBS)-based composite absorbing coating due to volume shrinkage during heat treatment is solved. The present invention provides a preparation method and application of an aluminum oxide-doped high-temperature resistant radar absorbing coating, which improves the density and high-temperature stability of the coating and provides a feasible technical approach for the lightweight and broadband design of high-temperature absorbing coatings at 700°C.
[0006] A method for preparing an aluminum oxide-doped high temperature resistant microwave absorbing coating comprises the following steps:
[0007] Step 1: Preparation of alumina-CBS glass-ceramics precursor.
[0008] Alumina and CBS glass-ceramics are mixed in proportion to obtain alumina-CBS glass-ceramics precursor powder with a particle size of ≤2 μm; wherein the amount of alumina doped accounts for 5 to 10 wt.% of the total mass of alumina and CBS glass-ceramics.
[0009] Step 2: Preparation of magnetic absorber-alumina-CBS glass-ceramic slurry.
[0010] The alumina-CBS glass-ceramics precursor obtained in step 1, the magnetic absorbent, polyethyleneimine (PEI) and the solvent are mixed to prepare a slurry for spray granulation, wherein the solid content of the slurry is 30-50wt.%.
[0011] The magnetic absorbent accounts for 10-25% of the total solid volume, PEI accounts for 1-5wt.% of the total solid mass, and the solid refers to the alumina-CBS microcrystalline glass precursor and the magnetic absorbent; the magnetic absorbent is a high temperature resistant magnetic absorbent (such as Fe-based), with a particle size less than 5μm and a Curie temperature greater than 700°C.
[0012] Step 3: Preparation of magnetic absorber-alumina-CBS glass-ceramics composite powder.
[0013] The slurry obtained in step 2 is spray granulated, dried, and screened to obtain a magnetic absorber-alumina-CBS glass-ceramic composite powder.
[0014] Step 4: Preparation of magnetic absorber-alumina-CBS glass-ceramics sprayed composite coating.
[0015] The surface of the target substrate is pretreated and cleaned, and an adhesive layer is prepared on the surface of the target substrate using atmospheric plasma spraying technology. The magnetic absorber-alumina-CBS glass-ceramic composite powder prepared in step 3 is then sprayed to obtain a corresponding sprayed composite coating.
[0016] Step 5: Preparation of magnetic absorber-alumina-CBS glass-ceramic composite coating.
[0017] The magnetic absorber-alumina-CBS glass-ceramics sprayed composite coating obtained in step 4 is subjected to a two-step heat treatment to obtain a magnetic absorber-alumina-CBS glass-ceramics composite coating.
[0018] Furthermore, the mixing method in step 1 is wet ball milling, so that the mixing effect of the alumina-microcrystalline glass precursor is better. The solid content of the slurry is 30-50wt.%; 2-5mm zirconia grinding balls are used, and the ball-to-material ratio is 2:1; the ball mill speed is 350-450RPM, and the ball milling mixing time is 24-48h; the ball milled slurry is dried at 100-120°C in an atmospheric environment.
[0019] Furthermore, the crystal structure of the aluminum oxide in step 1 is α-Al 2 O 3 ; Glass-ceramics is CaO-B 2 O 3 -SiO 2 Glass-ceramic, density less than 2.3g / cm 3 , dielectric constant is 5-6, and initial melting temperature is greater than 800℃.
[0020] Furthermore, in step 2, the mixing method adopts wet ball milling using a horizontal ball mill; the horizontal ball mill is selected because its kinetic energy is relatively low and will not produce strong external force on the shape of the magnetic absorber to make it flaky. Flaky powder will lead to poor compatibility with subsequent processing technology. For example, plasma spray curing causes the flaky magnetic absorber to be arranged in an orderly manner to form a relatively high electrical connectivity. The higher electrical connectivity has a negative impact on the magnetic absorbing performance due to the better conductivity.
[0021] Furthermore, in step 2, the solvent is a mixture of ammonia water and deionized water, and its pH value is 8-10, so as to facilitate volatilization by subsequent heating; and since PEI will undergo chemical changes in a strong alkaline environment (pH value ≥ 11), the pH value of the solvent is controlled.
[0022] Furthermore, the specific process of spray granulation in step 3 is as follows: the air inlet temperature of the spray granulator is 200-250°C, the air outlet temperature is 110-130°C, the feed rate is 20-40mL / min, and the atomizer frequency is 23-30Hz; subsequent drying is carried out at 120°C in the atmosphere, and after drying, the magnetic absorbent-alumina-CBS microcrystalline glass composite powder with a particle size of 40-80μm is sieved.
[0023] Furthermore, the fluidity of the magnetic absorbent-alumina-CBS glass-ceramic composite powder obtained in step 3 is not less than 80s / 50g.
[0024] Furthermore, the target substrate surface pretreatment in step 4 specifically includes rust removal of the target substrate by shot blasting, degreasing of the target substrate by kerosene, acetone, alcohol and deionized water in sequence, and finally sandblasting of the target substrate by corundum so that the surface of the target substrate has a uniform roughness.
[0025] Furthermore, the bonding layer is a NiCrAlY layer, and the atmospheric plasma spraying process parameters are: spraying distance is 120 mm, argon flow rate is 160 SCFH, nitrogen flow rate is 80 SCFH, hydrogen flow rate is 60 SCFH, powder feeding rate is 30 g / min; the bonding layer thickness is 60-100 μm.
[0026] Furthermore, the atmospheric plasma spraying process of the magnetic absorber-alumina-CBS microcrystalline glass sprayed composite coating in step 4 is: spraying distance 100-120 mm, argon flow rate 100-200 SCFH, nitrogen flow rate 60-100 SCFH, hydrogen flow rate 60-80 SCFH, powder feeding rate 10-25 g / min, spraying preheating temperature 200°C; during the cyclic spraying process, the current spraying surface temperature does not exceed 450°C, and the specifically designed absorbing coating thickness is achieved through cyclic spraying.
[0027] Furthermore, the two-step heat treatment in step 5 is specifically as follows: the atmosphere is argon, and the gas flow rate is 10-30 mL / min; the first step is to heat up to 800-830°C, keep warm for 2-5 hours, and the heating rate is 5-10°C / min; the second step is to heat up to 900-930°C, keep warm for 0.5-2 hours, and the heating rate is 1-4°C / min.
[0028] The two-step heat treatment is to reduce the cracking problem of the coating caused by thermal stress concentration due to direct rapid heating. In the first step of heating and heat preservation, a glass liquid phase is generated, which penetrates into the pores and cracks on the surface of the bonding layer through capillary force to improve the bonding strength of the coating, so that the Al in the alumina 3+ Ions diffuse into the glass matrix, inhibiting the β-CaSiO 3The crystallization of the coating promotes the formation of the liquid phase. The second step of heating is supplemented by a relatively slow heating rate to ensure a more uniform temperature gradient between the coating and the target substrate, reduce the concentration of thermal stress caused by local high temperature, and further reduce the viscosity of the glass liquid phase. The glass liquid phase infiltrates the magnetic absorber to form a dense protective film on its surface, and flows to the low-pressure area to fill the pores inside the coating and expel the air, thereby forming a denser coating. Ultimately, it avoids cracks or peeling caused by changes in thermal stress between the coating and the substrate due to high temperature in the application scenario.
[0029] In the present invention, a uniformly distributed alumina-glass-ceramic precursor is obtained through step 1 to ensure that the contact surface between alumina and CBS glass-ceramic is increased in the subsequent heat treatment so that the ions at the interface diffuse more fully. Step 2 is to obtain a radar absorbing coating with excellent performance, which requires the magnetic absorbent to be uniformly distributed inside the coating. However, the density of the magnetic absorbent is relatively large, and sedimentation will occur during the slurry preparation process. In an alkaline environment, the metal oxide layer formed by the magnetic absorbent and the surface of the alumina-CBS glass-ceramic precursor can absorb [OH] - , making the particle surface electronegative, improving the dispersibility of the magnetic absorber and the alumina-CBS glass-ceramic precursor under the action of electrostatic repulsion; at the same time, PEI is a cationic dispersant, which can be adsorbed on the particle surface to form a stable adsorption layer, forming a steric hindrance, further improving the dispersibility of the magnetic absorber and the alumina-CBS glass-ceramic precursor, and improving the stability of the slurry; and, during the spray granulation process, the viscosity of PEI increases after losing water, forming a sticky film on the particle surface, which can play a role in agglomerating the powder. Finally, the final CBS glass-ceramic-based high-temperature resistant wave-absorbing coating was obtained by the synergistic effect of PEI in an alkaline environment supplemented with ammonia water and alumina and CBS glass-ceramic through a two-step heat treatment.
[0030] In the two-step heat treatment process of the present invention, the formation of the CBS phase liquid phase at high temperature is regulated by controlling the alumina doping content, thereby avoiding the cracking and failure of the coating caused by the volume shrinkage of the CBS phase during the crystallization process. 3+ Ions can diffuse into the glass matrix through the alumina / CBS interface and combine with non-bridging oxygen in the glass to form stable [AlO 4 ] - In order to maintain the neutrality of the overall charge, the free cations in the glass matrix (such as Ca 2+ ) will participate in charge compensation, thus inhibiting the 3 The crystallization of aluminum oxide promotes the formation of liquid phase. However, due to the high melting point of aluminum oxide and the 3+The diffusion of Al2O3 in the glass matrix is limited. Therefore, when the content of Al2O3 is too high, the Al2O3 in the coating will hinder the flow of the glass liquid phase. However, at higher temperatures, CaAl2O3 will precipitate in the glass. 2 Si 2 O 8 phase, and β-CaSiO 3 In comparison, this phase has a smaller volume shrinkage and a lower dielectric constant, which further optimizes the structural stability and functionality of the coating.
[0031] In summary, the present invention solves the problem of coating cracking caused by volume shrinkage caused by crystallization during heat treatment of CBS-based absorbing coatings prepared by traditional atmospheric plasma spraying through a method of modifying CBS glass-ceramics by doping with alumina, further improves the density of the coating, prevents oxidation of Fe-based magnetic absorbers in high-temperature environments, improves the high-temperature stability of the coating, and facilitates the acquisition of alumina raw materials; the preparation method of the present invention has a simple process and is easy to industrialize, and has the advantages of lower density, wider radar absorption band and strong oxidation resistance compared to similar coatings, and can meet the requirements of stable use in a 700°C environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Optical photos of Examples 1-4 and Comparative Examples 1-4 after heat treatment;
[0033] Figure 2 This is a SEM image of the magnetic absorber-alumina-CBS glass-ceramic composite coating prepared in Example 1;
[0034] Figure 3 This is a test chart of the flat plate reflectivity of the radar absorbing coatings prepared in Examples 1-4 and Comparative Example 4 at room temperature;
[0035] Figure 4 This is a test graph of the flat plate reflectivity of the radar absorbing coating prepared in Example 1 at room temperature and 700°C;
[0036] Figure 5 This is a test graph of the flat plate reflectivity of the radar absorbing coating prepared in Example 1 after constant temperature oxidation at 700°C for 0h, 100h, 200h and 300h. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below through specific embodiments, comparative examples and accompanying drawings.
[0038] Example 1
[0039] The method for preparing the high temperature resistant microwave absorbing coating doped with aluminum oxide of this embodiment comprises the following steps:
[0040] Step 1: Preparation of alumina-CBS glass-ceramics precursor.
[0041] (1) weighing the raw materials so that the aluminum oxide accounts for 5 wt.% of the total mass of the aluminum oxide-CBS glass-ceramic powder;
[0042] (2) Alumina (crystal structure α-Al 2 O 3 ) and CBS glass-ceramic powder (CaO-B 2 O 3 -SiO 2 , Ca:Si:B molar ratio of 4:4:1.5) is added into a nylon ball mill, and deionized water and grinding balls (zirconia grinding balls, including 2mm and 5mm zirconia grinding balls) are added respectively for ball milling and mixing to obtain a mixed material; wherein the mass ratio of deionized water, zirconia grinding balls and alumina-CBS microcrystalline glass powder is 2:8:1, and the mass ratio of 2mm zirconia grinding balls to 5mm zirconia grinding balls is 2:1; the ball milling is carried out in a planetary ball mill at a speed of 400r / min for 48h; (3) the zirconia grinding balls in the mixed material obtained by ball milling are filtered, and the remaining components of the mixed material are dried in an atmospheric environment at 100°C to obtain an alumina-microcrystalline glass precursor.
[0043] Step 2: Preparation of magnetic absorber-alumina-CBS glass-ceramic slurry.
[0044] The alumina-CBS glass-ceramics precursor obtained in step 1, the magnetic absorbent, polyethyleneimine PEI and the solvent are mixed to prepare a slurry for spray granulation, wherein the solid content of the slurry is 50wt.%;
[0045] The magnetic absorbent accounts for 25 vol.% of the total solid volume, and PEI accounts for 2 wt.% of the total solid mass. The solid refers to alumina-CBS glass-ceramic precursor and magnetic absorbent; the magnetic absorbent is high temperature resistant Fe 90 Si 7 Cr 3 Magnetic absorber, with a particle size of less than 5μm and a Curie temperature greater than 700°C, to avoid oxidation in subsequent processes that may lead to deterioration of the absorption performance;
[0046] The mass ratio of zirconia grinding balls to magnetic absorbent-alumina-CBS glass-ceramic powder is 4:1; the solvent is a mixed solution of ammonia water and deionized water with a pH of 10; the ball milling is carried out in a horizontal ball mill with a rotation speed of 100 r / min and a time of 12 h.
[0047] After filtering the zirconium oxide grinding balls in the mixed material obtained by ball milling, the magnetic absorbent-alumina-CBS microcrystalline glass slurry is obtained.
[0048] Step 3: Preparation of magnetic absorber-alumina-CBS glass-ceramics composite powder.
[0049] (1) spray granulation of the slurry obtained by mixing in step 2; wherein the specific spray granulation process parameters are: air inlet temperature of 235° C., air outlet temperature of 115° C., atomizer frequency of 25 Hz, and feed rate of 20 mL / min.
[0050] (2) Drying the residual water vapor in the powder obtained by spray granulation in an atmosphere of 120° C., and using 40 μm and 80 μm sieves to obtain a magnetic absorbent-alumina-CBS glass-ceramic composite powder with a particle size of 40-80 μm.
[0051] Step 4: Preparation of magnetic absorber-alumina-CBS glass-ceramics sprayed composite coating.
[0052] (1) Surface pretreatment of the spraying substrate (made of 310 stainless steel): first, the surface rust layer was removed by shot peening, then kerosene, acetone, alcohol and deionized water were used to remove oil stains from the surface, and then the substrate was sandblasted with corundum to obtain a uniform surface roughness.
[0053] (2) A bonding layer is prepared on the substrate. The bonding layer is a NiCrAlY layer. The atmospheric plasma spraying process parameters are: spraying distance is 120 mm, argon flow rate is 160 SCFH, nitrogen flow rate is 80 SCFH, hydrogen flow rate is 60 SCFH, powder feeding rate is 30 g / min, and the bonding layer thickness is 80 μm.
[0054] (3) The magnetic absorber-alumina-CBS glass-ceramic composite powder obtained in step 3 is used to prepare a spray coating by atmospheric plasma spraying; wherein the specific spraying process parameters are: argon flow rate is 180 SCFH, nitrogen flow rate is 70 SCFH, argon flow rate is 50 SCFH, spraying power is 50 kW, and spraying distance is 100 mm; wherein the spraying preheating temperature is 200°C, and the temperature of the back side of the substrate does not exceed 450°C during the spraying process. The coating thickness reaches 1 mm through cyclic spraying, thereby obtaining a magnetic absorber-alumina-CBS glass-ceramic spray composite coating.
[0055] Step 5: Heat treatment of the magnetic absorber-alumina-CBS glass-ceramic composite coating.
[0056] The magnetic absorbent-alumina-CBS microcrystalline glass sprayed composite coating obtained in step 4 is placed in a tubular furnace for heat treatment: the heat treatment temperature is 800°C, kept for 5 hours, and the heating rate is 10°C / min; then it is increased from 800°C to 900°C and kept for 1 hour, and the heating rate is 2°C / min; the heat treatment atmosphere is argon, and the gas flow rate is 20mL / min. Finally, it is cooled to room temperature with the furnace and taken out to obtain the magnetic absorbent-alumina-CBS microcrystalline glass composite coating.
[0057] Example 2
[0058] The difference between Example 2 and Example 1 is that the added alumina content accounts for 7 wt.% of the total mass of the alumina-CBS glass-ceramics.
[0059] Example 3
[0060] The only difference between Example 3 and Example 1 is that the added alumina content accounts for 9wt.% of the total mass of the alumina-CBS glass-ceramics.
[0061] Example 4
[0062] The only difference between Example 4 and Example 1 is that the added alumina content accounts for 10wt.% of the total mass of the alumina-CBS glass-ceramics.
[0063] Comparative Example 1
[0064] The difference between Comparative Example 1 and Example 1 is that the content of added alumina accounts for 4 wt.% of the total mass of alumina-CBS glass-ceramics.
[0065] Comparative Example 2
[0066] The difference between Comparative Example 2 and Example 1 is that the content of added alumina accounts for 11 wt.% of the total mass of alumina-CBS glass-ceramics.
[0067] Comparative Example 3
[0068] The difference between this comparative example 3 and example 1 is that: a one-step method is used for heat treatment, the heat treatment temperature is 900°C, the heating rate is 10°C / min, the holding time is 1h, the heat treatment atmosphere is argon, the gas flow rate is 20mL / min, and finally the product is cooled to room temperature and taken out.
[0069] Comparative Example 4
[0070] The difference between Comparative Example 4 and Example 1 is that the solvent in step 2 is only deionized water.
[0071] The samples of Examples 1-4 and Comparative Example 4 were tested for performance, including temperature resistance, density and vertical reflectivity. There were no test results for Comparative Examples 1-4 because the coating cracked and failed after heat treatment (see Figure 1 ), so it is not included. The specific test characterization analysis is as follows:
[0072] The temperature resistance performance is 700℃ / 300h, cooled to room temperature, and the coating surface does not crack, crack or fall off as the qualified standard. The test results are shown in Table 1. The coating density is tested by the Archimedes method and the results are shown in Table 1.
[0073] Table 1:
[0074] Sample No. Temperature resistance <![CDATA[Density (g / cm 3 )]]> Example 1 qualified 3.79 Example 2 qualified 3.82 Example 3 qualified 3.84 Example 4 qualified 3.85 Comparative Example 4 qualified 3.73
[0075] It can be seen from Table 1 that the coatings of Examples 1-4 can be used for a long time at 700°C.
[0076] The main difference between Examples 1-4 and Comparative Examples 1-2 is the different doping contents of aluminum oxide. Figure 1 It can be seen that when the alumina content is lower than 5wt.% of the total volume of alumina-glass-ceramics, due to Al 3+ The ion content is low and the precipitation of β-CaSiO3 phase cannot be effectively suppressed, which leads to cracking of the coating. When the alumina content is lower than 10wt.% of the total volume of alumina-microcrystalline glass, due to the high melting point of alumina and effective diffusion, the alumina phase in the coating forms an obstacle to the glass liquid phase, making it impossible for the glass liquid phase to infiltrate the bonding layer and magnetic alloy, so the coating cracks.
[0077] The main difference between Example 1 and Comparative Example 3 is that different heat treatment methods are used. Figure 1 It can be seen that when the coating is rapidly heated to 900°C for heat treatment, the rapid change in temperature will cause the local stress of the coating to increase, resulting in cracking of the coating.
[0078] The main difference between Example 1 and Comparative Example 4 is the different solvent selections during the preparation of the magnetic alloy / alumina@microcrystalline glass slurry. Figure 3 As can be seen from the third column of Table 1, when the solvent is neutral, the radar absorption peak of the coating shifts to the right and the absorptivity decreases, and the density of the coating decreases, which indicates that the content of magnetic alloy in the coating is significantly reduced.
[0079] Figure 4 This is a comparison chart of the vertical reflectivity of Example 1 at room temperature and 700°C. The test results show that during the temperature change process, the vertical reflectivity changes slightly and can meet the requirements of use under high temperature.
[0080] Figure 5This is a comparison chart of the vertical reflectivity of Example 1 after 100h, 200h and 300h. The test results show that the radar absorption effect of the coating is stable, and the vertical reflectivity changes little after serving in a long-term high-temperature environment, which meets the application requirements.
[0081] It can be seen from the above embodiments that compared with the prior art, the alumina-doped high temperature resistant radar absorbing coating used in the present invention solves the problem of CaO-B 2 O 3 -SiO 2 The cracking problem of the base absorbing coating due to volume shrinkage during the heat treatment process. The density of the coating is improved through the heat treatment method, and the liquid phase CBS can infiltrate the adhesive layer and the magnetic alloy, thereby improving the high temperature stability of the coating. In addition, by adjusting the amount of alumina doping, the electromagnetic properties of the coating can be regulated within a certain range. At the same time, the method has the advantages of convenient raw material acquisition, green and environmentally friendly manufacturing process, and suitability for mass production. The above proves the feasibility of the alumina-doped high-temperature resistant absorbing coating prepared by the present invention.
Claims
1. A method for preparing an aluminum oxide-doped high temperature resistant radar absorbing coating, characterized in that: The following steps are involved: Step 1, preparing alumina-CBS glass-ceramics precursor; Alumina and CBS glass-ceramics are mixed in proportion to obtain an alumina-CBS glass-ceramics precursor powder with a particle size of ≤2 μm; wherein the amount of alumina doped accounts for 5 to 10 wt.% of the total mass of alumina and CBS glass-ceramics; Step 2, preparation of magnetic absorbent-alumina-CBS glass-ceramic slurry; The alumina-CBS glass-ceramics precursor obtained in step 1, the magnetic absorbent, polyethyleneimine PEI and the solvent are mixed to prepare a slurry for spray granulation, wherein the solid content of the slurry is 30-50wt.%; The magnetic absorbent accounts for 10-25% of the total volume of the solid, and PEI accounts for 1-5wt.% of the total mass of the solid. The solid refers to the alumina-CBS glass-ceramic precursor and the magnetic absorbent; the magnetic absorbent is a high temperature resistant magnetic absorbent, with a particle size of less than 5 μm and a Curie temperature greater than 700°C; Step 3, preparation of magnetic absorbent-alumina-CBS glass-ceramics composite powder; The slurry obtained in step 2 is spray granulated, dried, and screened to obtain a magnetic absorber-alumina-CBS glass-ceramic composite powder; Step 4, preparation of magnetic absorbent-alumina-CBS glass-ceramics sprayed composite coating; The target substrate surface is pre-treated and cleaned, and an adhesive layer is prepared on the target substrate surface by using an atmospheric plasma spraying technique, and then the magnetic absorber-alumina-CBS glass-ceramic composite powder prepared in step 3 is sprayed to prepare a corresponding sprayed composite coating; Step 5, preparation of magnetic absorber-alumina-CBS glass-ceramics composite coating; The magnetic absorber-alumina-CBS glass-ceramics sprayed composite coating obtained in step 4 is subjected to a two-step heat treatment to obtain a magnetic absorber-alumina-CBS glass-ceramics composite coating.
2. The method for preparing the aluminum oxide-doped high temperature resistant radar absorbing coating according to claim 1, characterized in that: The mixing method in step 1 is wet ball milling, so that the mixing effect of the alumina-microcrystalline glass precursor is better; wherein the solid content of the slurry is 30-50wt.%; 2-5mm zirconia grinding balls are used, and the ball-to-material ratio is 2:1; the ball mill speed is 350-450RPM, and the ball milling mixing time is 24-48h; the ball milled slurry is dried at 100-120°C in an atmospheric environment.
3. The method for preparing the aluminum oxide-doped high temperature resistant radar absorbing coating according to claim 1, characterized in that: The crystal structure of the aluminum oxide in step 1 is α-Al2O3; the glass-ceramics is CaO-B2O3-SiO2 glass-ceramics, and the density is less than 2.3 g / cm 3 , dielectric constant is 5-6, and initial melting temperature is greater than 800℃.
4. The method for preparing the aluminum oxide doped high temperature resistant radar absorbing coating according to claim 1, characterized in that: The mixing method in step 2 is wet ball milling using a horizontal ball mill.
5. The method for preparing the aluminum oxide doped high temperature resistant radar absorbing coating according to claim 1, characterized in that: The solvent in step 2 is a mixture of ammonia water and deionized water, and its pH value is 8-10.
6. The method for preparing the aluminum oxide doped high temperature resistant radar absorbing coating according to claim 1, characterized in that: The specific process of spray granulation in step 3 is as follows: the air inlet temperature of the spray granulator is 200-250°C, the air outlet temperature is 110-130°C, the feed rate is 20-40mL / min, and the atomizer frequency is 23-30Hz; subsequent drying is carried out at 120°C in the atmosphere, and after drying, the magnetic absorbent-alumina-CBS microcrystalline glass composite powder with a particle size of 40-80μm is sieved.
7. The method for preparing the aluminum oxide doped high temperature resistant radar absorbing coating according to claim 1, characterized in that: The fluidity of the magnetic absorbent-alumina-CBS glass-ceramic composite powder obtained in step 3 is not less than 80s / 50g.
8. The method for preparing the aluminum oxide doped high temperature resistant radar absorbing coating according to claim 1, characterized in that: The bonding layer is a NiCrAlY layer, and the atmospheric plasma spraying process parameters are: spraying distance is 120mm, argon flow rate is 160SCFH, nitrogen flow rate is 80SCFH, hydrogen flow rate is 60SCFH, powder feeding rate is 30g / min; the bonding layer thickness is 60-100μm.
9. The method for preparing the aluminum oxide doped high temperature resistant radar absorbing coating according to claim 1, characterized in that: The atmospheric plasma spraying process of the magnetic absorber-alumina-CBS microcrystalline glass sprayed composite coating in step 4 is: spraying distance 100-120mm, argon flow rate 100-200SCFH, nitrogen flow rate 60-100SCFH, hydrogen flow rate 60-80SCFH, powder feeding rate 10-25g / min, spraying preheating temperature 200°C; during the cyclic spraying process, the current spraying surface temperature does not exceed 450°C, and the specifically designed absorbing coating thickness is achieved through cyclic spraying.
10. The method for preparing the aluminum oxide doped high temperature resistant radar absorbing coating according to claim 1, characterized in that: The two-step heat treatment in step 5 is specifically as follows: the atmosphere is argon, and the gas flow rate is 10-30 mL / min; the first step is to heat up to 800-830°C, keep warm for 2-5 hours, and the heating rate is 5-10°C / min; the second step is to heat up to 900-930°C, keep warm for 0.5-2 hours, and the heating rate is 1-4°C / min.
Citation Information
Patent Citations
High temperature-resistant electromagnetic wave-absorbing coating and use thereof
CN106497313A
Reinforced calcium borosilicate microcrystalline glass composite material and preparation method thereof
CN110683769A
Magnetic composite absorbent suitable for thermal spraying, preparation method and application
CN115926516A
Magnetic alloy / glass ceramic composite powder for thermal spraying, preparation method of magnetic alloy / glass ceramic composite powder and radar wave-absorbing coating
CN117165111A
Ferromagnetic absorbent with hollow porous microsphere structure and preparation method thereof
CN117567983A
Cited By
High-temperature-resistant radar wave-absorbing coating and preparation method thereof
CN120738642A